(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Electrochemical discharge Machining (ECDM)is non conventional hybrid machining process, which is used for nonconductive material like glass, composite, quartz for micro machining in aerospace, medical, agriculture, optical. electronics applications.